Role of Sertaconazole in the Treatment of Dermatophytosis (Medicine Today, 2024)
Dermatophytosis is a major health burden worldwide and is now increasing day by day. Dermatophytosis is also becoming increasingly unresponsive to topical conventional antifungals now a day. Newer topical antifungals may be more effective in these patients. Sertaconazole is a new, broad spectrum, fungicidal and fungistatic imidazole with added antipruritic and anti-inflammatory activity that may be effective and beneficial in improving the quality of life for the patient with dermatophytoses. It is indicated in the European Union(EU) for the treatment of superficial skin mycoses such as dermatophytosis (including tinea corporis, tinea cruris, tinea manus, tinea barbae and tinea pedis), cutaneous candidiasis, pityriasis versicolor and seborrhoeic dermatitis of the scalp, and in the US for tinea pedis only. Sertaconazole has broad-spectrum antifungal activity against dermatophytes of the Trichophyton, Epidermophyton and Microsporum genera, and yeasts of the genera Candida and Cryptococcus; additionally, it is effective against opportunistic filamentous fungi and Gram-positive bacteria. Moreover, the antifungal activity of sertaconazole is maintained in clinical isolates of dermatophytes that show reduced susceptibility to other azoles. While the drug has good dermal penetration, this is not associated with systemic absorption. In clinical trials in patients with superficial mycoses, 2% sertaconazole cream applied twice daily was effective in the eradication of a range of dermatophytoses, and a significantly greater proportion of patients were cured compared with those receiving 2% miconazole cream twice-daily treatment. Both as a topical cream and suppository preparation, sertaconazole was generally well tolerated. Sertaconazole is a well-established antifungal agent, which is now available in a variety of formulations, and remains a useful treatment option particularly in patients with fungal infections resistant to other azoles.Medicine Today 2023 Vol.36 (1): 62-66